1949
DOI: 10.1084/jem.90.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Isolation From Cases of Infantile Diarrhea of a Filtrable Agent Causing Diarrhea in Calves

Abstract: From instances of diarrhea of the newborn in four separate hospital outbreaks a filtrable agent was isolated which regularly produced diarrhea in calves. This agent appeared to have the characteristics of a filtrable virus. The four strains of virus isolated in the outbreaks studied appeared to be identical or very closely related. The virus was not found present in the stools of any of eight normal newborn infants or five normal calves. Evidence is presented that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1950
1950
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…t Two of these patients had Salmonella and one had EPEC in stool culture. 4 One of these patients had Shigella in stool culture.…”
Section: Resultsmentioning
confidence: 99%
“…t Two of these patients had Salmonella and one had EPEC in stool culture. 4 One of these patients had Shigella in stool culture.…”
Section: Resultsmentioning
confidence: 99%
“…After initial passage in calves, Light and Hodes were able to perform from 2 to 29 successive calf passages by intranasal inoculation using unfiltered or Seitz-filtered stool specimens. Subsequent studies by electron microscopy of a lyophilized fecal specimen from a calf used in the original study of Light and Hodes (65,66), revealed viral particles of similar size and morphology as rotavirus (46). Although attempts to reproduce the disease in a calf using the lyophilized specimen were unsuccessful, the ability of human rotavirus to cause diarrhea in calves was confirmed in a study by Mebus et al.…”
Section: P R O C E D U R Ementioning
confidence: 93%
“…After the work of Light and Hodes (65,66), rotaviruses were isolated from several other animal species, including the viruses responsible for epizootic diarrhea of infant mice (EDIM) (1,15,60), simian virus SA11 from Cercopithecus monkeys and the O {Offal) agent {63,70), and Nebraska calf diarrhea virus (NCDV) from cattle {30, 78,79). The successful reproduction and passage of caff diarrhea (scours) in experimental calves was first accomplished by Mebus et al {79).…”
Section: P R O C E D U R Ementioning
confidence: 99%